The Orion Center bibliography of the Dead Sea scrolls (1995-2000) - Pinnick, Avital. (Studies on the Texts of the Desert of Judah, 2001)
The Orion Center Bibliography of the Dead Sea Scrolls (1995-2000) is the fourth official Scrolls bibliography, following bibliographies covering the periods 1948-1957 (W. S. LaSor), 1958-1969 (B. Jongeling), and 1970-1995 (F. García Martínez and D. W. Parry). The current interest in the Scrolls, with at least two journals dedicated to these texts, has led to a proliferation of secondary literature, theses, and electronic publications. The Orion Center Bibliography contains over 3000 entries, including approximately 600 reviews, gathered from the École Biblique et Archéologique Française in Jerusalem, from on-line databases, and from the authors themselves. This work is based on the bibliography compiled by the Orion Center for the Study of the Dead Sea Scrolls, Jerusalem, and includes reviews, journal articles, and electronic publications, a text index and a subject index.